2018
DOI: 10.1186/s13662-018-1826-1
|View full text |Cite
|
Sign up to set email alerts
|

On the solutions of a max-type system of difference equations with period-two parameters

Abstract: In this paper, we study the following max-type system of difference equations:where A n , B n ∈ (0, +∞) are periodic sequences with period 2 and the initial values x -1 , y -1 , x -2 , y -2 ∈ (0, +∞). We show that every solution of the above system is eventually periodic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In [25], Su et al, inspired by above results of (1.4), investigated the periodicity of positive solutions of the following max-type systems of difference equations…”
Section: Introductionmentioning
confidence: 99%
“…In [25], Su et al, inspired by above results of (1.4), investigated the periodicity of positive solutions of the following max-type systems of difference equations…”
Section: Introductionmentioning
confidence: 99%
“…e study of the system of max-type di erence equations attracted recently a considerable attention; see, for example, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], and the references listed therein. is type of difference equations stemming from, for example, certain models are useful in automatic control theory (see [27]).…”
Section: Introductionmentioning
confidence: 99%
“…with A, B ∈ R + and showed that every positive solution of the above system is eventually periodic. Further, Su et al [18] studied eventual periodicity of the following max-type system of difference equations:…”
Section: Introductionmentioning
confidence: 99%